SERINC5 can enhance proinflammatory cytokine production by primary human myeloid cells in response to challenge with HIV-1 particles - Pierini, Virginia; Gallucci, Lara; Stürzel, Christina; Kirchhoff, Frank; Fackler, Oliver Till (Journal of virology, 2021)
HIV-1 has to overcome physical barriers posed by host cell restriction factors (RFs) for efficient replication. Some RFs, including Trim5α and tetherin, trigger antiviral signaling in addition to directly impairing HIV replication. SERINC5 (S5) is an RF that is incorporated into HIV-1 particles to potently impair their infectivity and is efficiently antagonized by the viral pathogenesis factor Nef. Since effects of S5 on HIV-1 infectivity were mostly studied in reporter cell lines, we analyzed the effects of S5 during infection of primary HIV-1 target cells. In activated CD4+ T lymphocytes, virion incorporation of S5 only moderately impaired virion infectivity and was not associated with altered innate immune recognition. In contrast, in monocyte-derived macrophages, S5 virion incorporation potentiated the production of proinflammatory cytokines with very potent but donor-dependent effects on virion infectivity. Nef counteracted effects of S5 on both cytokine production and virion infectivity. Similar S5-induced cytokine production was observed in immature monocyte-derived dendritic cells. Notably, S5-mediated enhancement of cytokine production was not linked to the efficacy of productive infection and could be overcome by using vesicular stomatitis virus glycoprotein (VSV-G) but not infectivity restriction-insensitive HIV-1 Env for cell entry. Moreover, inhibiting entry of S5-negative HIV-1 ΔNef particles increased proinflammatory cytokine production comparably to virion incorporation of S5. Together, these results describe the sensitization of noninfectious HIV-1 particles to proinflammatory cytokine production by myeloid target cells as an additional and Nef-sensitive activity of S5. Moreover, the study reveals important cell-type and donor-dependent differences in the sensitivity of HIV target cells for antiviral effects of S5. IMPORTANCE SERINC5 (S5) is a host cell restriction factor (RF) that impairs the infectivity of HIV-1 particles in target cell lines. To assess the potential physiological relevance of this restriction, we assessed the effects of S5 on HIV-1 infection of relevant primary human target cells. We found that effects of S5 on infection of CD4+ T lymphocytes were negligible. In myeloid target cells, however, virion incorporation of S5 potently suppressed infectivity and promoted innate immune recognition of HIV-1 particles characterized by proinflammatory cytokine production. Both effects were not observed in cells of all donors analyzed, were exerted independently of one another, and were counteracted by the HIV-1 pathogenesis factor Nef. These results identify the sensitization of HIV-1 particles for innate immune recognition by myeloid target cells as a novel activity of S5 and emphasize the need to study RF function in the context of primary target cells and taking donor variabilities into account.
Gesehen am 28.04.2022